Self-medication practice and associated socio-demographic variables among adult in Morang district of Miklajung rural municipality - Poudyal, Aassmi; Nepal, Susmita (International Journal Of Community Medicine And Public Health, 2021)
Background: Self-medication is the selection and use of medicine to treat self-recognized illness. The study’s main purpose was to evaluate the self-medication practice and its associated socio-demographic factors. Methods: A cross-sectional study design was conducted in the Miklajung rural municipality of Morang district. A total of 408 households were selected by systematic random sampling. Participants from age 19-59 years old who had self-medicated for acute diseases in the last three months were included in the study. A semi-structured questionnaire was used as a tool to collect information regarding self-medication. All data extracted from questionnaires were entered and analyzed using SPSS version 20, for the association chi-square test was done. Results: The overall prevalence of self-medication practice in last three months was 61.5%. The most common acute disease for self-medication was common cold 70.5%. More than 50 % of participants had used painkillers as medicine which was brought from the pharmacy, and the source of information on medicine was obtained from pharmacists. The main reason for self-medication practice was due to respondents perceiving illness as minor and cost of health services. The self-medication practice was found associated with occupation, marital status and wealth quintile with p value 0.01, 0.04 and 0.02 respectively. Conclusions: The study revealed a high prevalence of self-medication practice among the adult. There was an association between self-medication practice and socio-demographic factors. People should be educated about the risk and benefit of self-medication practice.